4E analyses of novel dual-heat source/sink ejector-compression heat pump system. (June 2021) - Liu, Jian; Tian, Xue; Lin, Zhang
Abstract: For improving the indoor thermal comfort and air quality, floor radiant heating and cooling combined with fresh air systems have been widely used in recent years. These systems require two heat sources/sinks at different temperatures. To satisfy the requirement of two heat sources/sinks, an ejector-compression dual-heat source/sink air source heat pump (EDHP) system was developed in this study, which provides two heat sources/sinks at different temperatures under heating/cooling conditions. Theoretical models were established to analyze the energetic, exergetic, economic, and environmental (4E) performance of the proposed system in comparison with a conventional dual-heat source/sink air source heat pump (CDHP) system. The effects of different parameters on the performances of the systems were investigated. The results indicated that the EDHP system had significant advantages over the CDHP system regarding the 4E indicators. Under the cooling mode, compared with the CDHP system, the coefficient of performance ( COP ), cooling capacity per unit volume ( q v ), and exergy efficiency ( ƞ ex ) of the EDHP system were improved by 17.7%–28.9%, 18.1%–36.7%, and 13.4%–35.1%. Additionally, the economic and environmental performances of the EDHP system were improved significantly. When the high-grade heat source/sink load ratio (LR ) was 0.5, the annual investment and maintenance cost rate, annual operation cost rate, total annual cost rate, and CO2 emissions were reduced by 14.1%, 17.9%, 17.4%, and 20.5%. The results indicated that the EDHP system has considerable potential for energy saving, exergy efficiency improvement, environmental benefit, and cost reduction. It also provided a base for the application and optimization of the EDHP system in future work. Highlights: A ejector-compression dual-heat source/sink heat pump (EDHP) system was proposed. 4E analysis results indicated EDHP system outperforms the conventional system. An internal heat exchanger (IHX) was introduced to improve the EDHP system. Reducing the high-grade heat source demand enhances the EDHP system performance significantly.